Cavity‐backed bow‐tie antenna with dielectric loading for ground‐penetrating radar application. Issue 2 (18th November 2019) - Liu, Shufang; Li, Mengqian; Li, Huimin; Yang, Linna; Shi, Xiaowei
Abstract : Bow‐tie antennas are widely used in practical ground‐penetrating radars. In spite of simple structure and wideband characteristics, boresight gain of the antenna is small and the radiation pattern is omnidirectional. In this study, a cavity‐backed bow‐tie antenna with dielectric loading is presented. The bow‐tie antenna is resistively loaded to reduce ringing effects. The resistively loaded antenna is placed within a rectangle cavity, which acts as a reflector, for unidirectional radiation and high gain. A dielectric is loaded on the antenna aperture to enlarge the operational bandwidth and stabilise the radiation patterns. Parameter studies of the dielectric substrate are performed to optimise the antenna performance. The final design is fabricated and measured. It has been shown that the antenna exhibits wide impedance bandwidth of 120% for VSWR ≤ 2 . The boresight gain is more than 5 dBi. The radiation patterns are stable and unidirectional over the whole band, and the late‐time ringing is small.